Tunable Anisotropic Wettability of Rice Leaf‐Like Wavy Surfaces. (7th September 2012) - Lee, Seung Goo; Lim, Ho Sun; Lee, Dong Yun; Kwak, Donghoon; Cho, Kilwon
Abstract Rice leaves can directionally shed water droplets along the longitudinal direction of the leaf. Inspired by the hierarchical structures of rice leaf surfaces, synthetic rice leaf‐like wavy surfaces are fabricated that display a tunable anisotropic wettability by using electrostatic layer‐by‐layer assembly on anisotropic microwrinkled substrates. The nanoscale roughness of the rice leaf‐like surfaces is controlled to yield tunable anisotropic wettability and hydrophobic properties that transitioned between the anisotropic/pinned, anisotropic/rollable, and isotropic/rollable water droplet behavior states. These remarkable changes result from discontinuities in the three‐phase (solid–liquid–gas) contact line due to the presence of air trapped beneath the liquid, which is controlled by the surface roughness of the hierarchical nanostructures. The mechanism underlying the directional water‐rolling properties of the rice leaf‐like surfaces provides insight into the development of a range of innovative applications that require control over directional flow.